1995
DOI: 10.1002/ajmg.1320570240
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biology of the neuronal ceroid‐lipofuscinoses (NCL): An overview

Abstract: Multiple forms of ceroid-lipofuscinosis occur in human beings and animals. They are characterized by brain and retinal atrophy associated with selective necrosis of neurons. This neurodegenerative disease appears associated with the disease process rather than storage of fluorescent lipopigment per se, and there is now growing evidence that pathogenesis may involve mitochondria rather than a primary defect of lysosomal catabolism. Of the forms of ceroid-lipofuscinosis studied, most but not all reflect accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Although human and animal NCLs result from mutations in more than eight different genes, they are all characterized by massive accumulations of autofluor- (Jolly 1995;Katz et al 1997;Wisniewski et al 2001). In all types of NCL that have been characterized to date, the storage bodies have been reported to contain predominantly a single protein or a few major proteins: F 0 subunit c of mitochondrial ATP synthase, vacuolar V 0 ATPase subunit c, or saposins A and D (Palmer et al 1986(Palmer et al , 1989(Palmer et al , 1990(Palmer et al , 1997Tyynela et al 1993Tyynela et al , 1997a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although human and animal NCLs result from mutations in more than eight different genes, they are all characterized by massive accumulations of autofluor- (Jolly 1995;Katz et al 1997;Wisniewski et al 2001). In all types of NCL that have been characterized to date, the storage bodies have been reported to contain predominantly a single protein or a few major proteins: F 0 subunit c of mitochondrial ATP synthase, vacuolar V 0 ATPase subunit c, or saposins A and D (Palmer et al 1986(Palmer et al , 1989(Palmer et al , 1990(Palmer et al , 1997Tyynela et al 1993Tyynela et al , 1997a.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal ceroid lipofuscinoses (NCLs) are inherited neurodegenerative disorders characterized by massive accumulations of autofluorescent storage material in neurons and other cell types (Haltia 2006;Jolly 1995;Katz et al 1997;Seehafer and Pearce 2006;Wisniewski et al 2001). A distinctive feature of the NCLs is that the stored material contains predominantly a single protein or relatively few specific proteins (Haltia 2006;Palmer et al 1986Palmer et al , 1989Palmer et al , 1990Palmer et al , 1997Tyynela et al 1993Tyynela et al , 1997a.…”
Section: Introductionmentioning
confidence: 99%
“…The electrophysiologic, biochemical, light microscopic, and ultrastructural characteristics of human and experimental canine NCL have been reviewed extensively elsewhere, but reports describing the features of spontaneous canine CL are rare in veterinary literature. 1,2,4,9,13 This report describes the clinical, light microscopic, and electron microscopic features of NCL in a geriatric Labrador Retriever, a breed not previously associated with canine NCL.…”
mentioning
confidence: 94%
“…The electrophysiologic, biochemical, light microscopic, and ultrastructural characteristics of human and experimental canine NCL have been reviewed extensively elsewhere, but reports describing the features of spontaneous canine CL are rare in veterinary literature. 1,2,4,9,13 This report describes the clinical, light microscopic, and electron microscopic features of NCL in a geriatric Labrador Retriever, a breed not previously associated with canine NCL.An 8-year-old, neutered male Labrador Retriever was presented for evaluation of progressive partial seizure activity, characterized by facial and ear twitching, of 11-months duration. In the 2 weeks before referral, the owners reported that the dog had also become ataxic and dysphagic and that the facial twitching occurred multiple times daily.…”
mentioning
confidence: 99%
See 1 more Smart Citation